Self-organization of river vegetation leads to emergent buffering of river flows and water levels - Cornacchia, Loreta; Wharton, Geraldene; Davies, Grieg; Grabowski, Robert C.; Temmerman, Stijn; van der Wal, Daphne; Bouma, Tjeerd J.; van de Koppel, Johan (The Royal Society, 2020)
Global climate change is expected to impact hydrodynamic conditions in stream ecosystems. There is limited understanding of how stream ecosystems interact and possibly adapt to novel hydrodynamic conditions. Combining mathematical modelling with field data, we demonstrate that bio-physical feedback between plant growth and flow redistribution triggers spatial self-organization of in-channel vegetation that buffers for changed hydrological conditions. The interplay of vegetation growth and hydrodynamics results in a spatial separation of the stream into densely vegetated, low-flow zones divided by unvegetated channels of higher flow velocities. This self-organization process decouples both local flow velocities and water levels from the forcing effect of changing stream discharge. Field data from two lowland, baseflow-dominated streams support model predictions and highlight two important stream-level emergent properties: vegetation controls flow conveyance in fast-flowing channels throughout the annual growth cycle, and this buffering of discharge variations maintains water depths and wetted habitat for the stream community. Our results provide important evidence of how plant-driven self-organization allows stream ecosystems to adapt to changing hydrological conditions, maintaining suitable hydrodynamic conditions to support high biodiversity
Keywords: submerged aquatic macrophytes; flow regulation; spatial self-organization; bio-physical feedbacks